2017
DOI: 10.18632/oncotarget.22752
|View full text |Cite
|
Sign up to set email alerts
|

Induction of oxidative stress and cell apoptosis by selenium: the cure against oral carcinoma

Abstract: Oral carcinoma (OC) remains one of the most difficult malignancies to cure. selenium (Se) is an essential trace mineral for human and animals, but high concentrations of Se induce apoptosis and oxidative effects. Although cell apoptosis has been evidenced as a critical mechanism mediating the anticancer activity of Se, the underlying molecular mechanisms remain elusive. To explore the role of Se in rat OC, we examined the weather the oxidative stress-mediated apoptotic pathway induced by Se was involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…15 and molecular pathogenesis of KBD. Inadequate selenium nutritional status has also been linked to a variety of human diseases, including cancer and cardiovascular disease (33,34).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…15 and molecular pathogenesis of KBD. Inadequate selenium nutritional status has also been linked to a variety of human diseases, including cancer and cardiovascular disease (33,34).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Kim et al 3 . and Qiao et al 58 . showed that high concentrations of selenium induce apoptosis, although it is a basic element.…”
Section: Discussionmentioning
confidence: 91%
“…This compound has recently attracted many researchers' attention to investigate the potential antimicrobial possibility of its organic and synthetic elements. Here, we decided to evaluate the induction of apoptosis of HESA-A in Leishmania major promastigotes in vitro since several reports on the effects of various elemental components of HESA-A in inducing oxidative stress and cell apoptosis in cancer cells (38). Apoptosis is a strategy for the treatment of cancer cells;…”
Section: Discussionmentioning
confidence: 99%